Abuse of Market Dominance in Indonesia's Rice Industry: A Legal Analysis of PT Wilmar Padi's Alleged Price Monopoly - Tribhuwana Kameswari, Ganis (Jurnal Hukum In Concreto, 2024)
This study analyzes the alleged abuse of dominant position by PT Wilmar Padi in the rice market under Article 25 of Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. Employing a normative legal method and a qualitative case study, the research investigates whether the company’s market conduct fulfills the criteria of dominance abuse in competition law. The analysis draws on primary legal sources, policy documents, and academic literature to examine the structure of the rice supply chain and regulatory enforcement. The findings reveal that PT Wilmar Padi exercises substantial market power in procurement and pricing, potentially limiting competition and harming smallholder farmers. The study also identifies several institutional limitations faced by the Business Competition Supervisory Commission (KPPU), including insufficient data access, weak inter-agency coordination, and limited sector-specific expertise. While the legal framework formally prohibits abuse of dominance, enforcement remains underdeveloped in agricultural commodity markets. The paper recommends strengthening institutional capacity, adopting clearer legal guidelines for the agricultural sector, and promoting cross-agency collaboration. These steps are critical to ensuring that competition law contributes to equitable, transparent, and sustainable market governance.